Historical And Spiritual Ideals And Them Social-Pedagogical Need For Development Of Axiological Attitude - Tursunova Dilnoza Adhamjon kizi (Euro Asian Journal Publishing, 2023)
In this article, opinions are expressed about the socio-pedagogical necessity of developing historical and spiritual ideals and axiological relation to them. Also, the article contains some ideas, suggestions and recommendations that can be used in the methodology of teaching history
Keywords: Historical and spiritual ideals; axiological attitude; methodology